The impact of affectivity on learning English in the University Context (Educational Knowledge, 2024)
When students transition to higher education with an insufficient grasp of foundational English language concepts—whether due to the absence of a specialized instructor, the substitution of the subject with alternative coursework, or the assignment of a teacher whose profile diverges from the requisite for foreign language pedagogy—the resultant lack of these linguistic fundamentals poses a detrimental impact on the commencement of their university journey. Consequently, students find themselves devoid of the requisite knowledge to underpin their academic development. This dearth manifests in the expression of mistrust, insecurity, and demotivation towards the study of the English language among university cohorts.To surmount this challenge and cultivate students’ fearless engagement in the learning process, it becomes imperative to furnish them with a conducive environment where they perceive robust support. This necessitates endowing them with the essential cognitive tools to comprehend that mastering a foreign language, such as English, not only opens avenues for professional advancement but also enhances employability prospects. Within the framework of this research, the affective component assumes significance as a pivotal factor influencing students within a semi-rural context. The establishment of a congenial atmosphere during English classes underscores that the language acquisition experience can be gratifying without the imposition of punitive measures inhibiting their involvement in assigned activities
Keywords: Language acquisition; Higher education; English proficiency; Affective component; Academic motivation